Polyiodide Confinement by Starch Enables Shuttle‐Free Zn–Iodine Batteries - Zhang, Shao‐Jian; Hao, Junnan; Li, Huan; Zhang, Peng‐Fang; Yin, Zu‐Wei; Li, Yu‐Yang; Zhang, Bingkai; Lin, Zhan; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2022)
Aqueous Zn–iodine (Zn–I2) batteries have been regarded as a promising energy‐storage system owing to their high energy/power density, safety, and cost‐effectiveness. However, the polyiodide shuttling results in serious active mass loss and Zn corrosion, which limits the cycling life of Zn–I2 batteries. Inspired by the chromogenic reaction between starch and iodine, a structure confinement strategy is proposed to suppress polyiodide shuttling in Zn–I2 batteries by hiring starch, due to its unique double‐helix structure. In situ Raman spectroscopy demonstrates an I5−‐dominated I−/I2 conversion mechanism when using starch. The I5− presents a much stronger bonding with starch than I3−, inhibiting the polyiodide shuttling in Zn–I2 batteries, which is confirmed by in situ ultraviolet–visible spectra. Consequently, a highly reversible Zn–I2 battery with high Coulombic efficiency (≈100% at 0.2 A g−1) and ultralong cycling stability (>50 000 cycles) is realized. Simultaneously, the Zn corrosion triggered by polyiodide is effectively inhibited owing to the desirable shuttling‐suppression by the starch, as evidenced by X‐ray photoelectron spectroscopy analysis. This work provides a new understanding of the failure mechanism of Zn–I2 batteries and proposes a cheap but effective strategy to realize high‐cyclability Zn–I2 batteries. Inspired by the significant chromogenic reaction between starch and iodine, the shuttle effect of Zn–I2 batteries is effectively addressed by using starch, which strongly anchors polyiodide anions due to its unique double‐helix structure. Benefiting from this structure confinement, a Coulombic efficiency of almost 100% and an ultralong life of 50 000 cycles are realized in Zn–I2 batteries.